A new species and new records of Paryphoconus from the Amazon region of Peru (Diptera: Ceratopogonidae) - Melina Mauad; Gustavo R. Spinelli (Revista Mexicana de Biodiversidad)
Paryphoconus peruvianus, a new species from Peruvian Amazonia is described and illustrated from female and male specimens collected at light in the Department of Cuzco. The species is compared with its similar congener P. anomalicornis Kieffer. Furthermore, P. anomalicornis, P. fusciradialis Spinelli y Wirth and P. oliveirai Lane are firstly recorded from Peru.